Bezradni świadkowie trudnych sytuacji w przedszkolu. Refleksje studentów wczesnej edukacji odbywających praktyki - Maria Groenwald; Anna Babicka-Wirkus (Problemy Wczesnej Edukacji)
This paper addresses the issue of these experiences collected by early education students of the University of Gdańsk and the Pomeranian Academy in Słupsk during teacher training in kindergarten which they specified as hard and presented in essays. Subjecting the events described to a qualitative analysis made it possible to unravel that (a) students find hard instances of children being harmed by teachers, particularly being treated with violence; (b) teacher trainees participate in these incidents as passive, helpless witnesses, as they do not know ways of protecting kindergarten children against maltreatment; (c) it is necessary to better prepare teachers-to-be for resolution of hard situations with children’s participation.